A Novel Algorithm for Indirect Reputation-Based Grid Resource Management - Echaiz, Javier; Ardenghi, Jorge R.; Simari, Guillermo R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
A computational grid is a distributed infrastructure that appears to the end user as one large computing resource across organization boundaries. Grid technologies enable large-scale sharing of resources within formal or informal consortia of individuals and/or institutions, usually called virtual organizations. In these settings, the discovery, characterization, management, and monitoring of resources, services, and computations can be challenging due to the considerable diversity, large numbers, dynamic behavior, and geographical distribution of the entities in which a user might be interested. Trust is one of the biggest concerns in the grid resource management field. Grid systems can employ reputation mechanisms in order to provide this essential trust, but not usually without incurring in certain additional costs that negate the potential performance gains offered by grid computing technologies. Moreover, current reputation mechanisms are not appropriate for resource management in large-scale systems. In this paper, we present a new reputation model for resource management based on a economy model. Also we demonstrate how it can by employed to add trust into algorithms for grid scheduling. Finally, we simulate the proposed resource management algorithm in order to verify its effectiveness.